2020
DOI: 10.3150/19-bej1137
|View full text |Cite
|
Sign up to set email alerts
|

Tail expectile process and risk assessment

Abstract: Expectiles define a least squares analogue of quantiles. They are determined by tail expectations rather than tail probabilities. For this reason and many other theoretical and practical merits, expectiles have recently received a lot of attention, especially in actuarial and financial risk management. Their estimation, however, typically requires to consider non-explicit asymmetric least squares estimates rather than the traditional order statistics used for quantile estimation. This makes the study of the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
65
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 45 publications
(90 reference statements)
3
65
0
Order By: Relevance
“…Second, Theorem 2 in Daouia et al [15] unravels the discrepancy between the tail empirical expectile process and its population counterpart. As these two theorems constitute the basic theoretical tools for our asymptotic analysis in the present paper, they are briefly described below in Proposition 1 along with the statistical model in Section 2.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Second, Theorem 2 in Daouia et al [15] unravels the discrepancy between the tail empirical expectile process and its population counterpart. As these two theorems constitute the basic theoretical tools for our asymptotic analysis in the present paper, they are briefly described below in Proposition 1 along with the statistical model in Section 2.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly to this intuitive tail conditional expectation, Taylor [45] has introduced and used the expectile-based form ErY |Y ą ξ τ s as the basis for estimating the standard quantilebased measure ErY |Y ą q τ s. Given that both conditional expectations ErY |Y ą q τ s and ErY |Y ą ξ τ s are not coherent risk measures in general, Daouia et al [15] have suggested to estimate the coherent ES form QES τ on the basis of its expectile-based analogue XES τ :" 1 1´τ…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations